Identification of USP39 as a prognostic and predictive biomarker for determining the response to immunotherapy in pancreatic cancer - Jiahui Yuan; Beibei Xu; Yongcheng Su; Pingping Zhang; Xianbin Zhang; Peng Gong (BMC Cancer)
Abstract Ubiquitin-Specific Protease 39 (USP39) has been implicated in numerous malignancies, however, its pathogenic mechanisms and impact on the tumor immune microenvironment (TIME) remain incompletely characterized. Based on The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) databases, we investigated the diagnostic and prognostic values of USP39 across various cancer types. Additionally, we examined the correlation between USP39 expression and immune-related gene signature, immune cell infiltration pattern, tumor microsatellite instability (MSI), and tumor mutation burden (TMB). This study specifically focused on exploring the clinical relevance and molecular functions of USP39 in pancreatic adenocarcinoma (PAAD), with particularly emphasis on its role in shaping the TIME and modulating responses to immunotherapy. The results demonstrated that evaluated USP39 expression significantly correlated with advanced tumor stage and unfavorable clinical outcomes across multiple cancer types, most notably in PAAD. Functional enrichment analysis indicated that USP39 potentially promotes tumor progression through multiple oncogenic signaling cascades. In vitro experimental validation confirmed that USP39 knockdown inhibited migration and proliferation of pancreatic cancer cells while inducing apoptosis. Additionally, we identified significant positive correlations between USP39 expression and immune checkpoint molecules, particularly prominent in PAAD. Furthermore, we observed associations between USP39 expression and TMB in 16 cancer types and MSI in 11 cancer types, suggesting that heightened USP39 expression may enhance responsiveness to immunotherapeutic interventions. Collectively, our findings establish USP39 as a valuable immune-related biomarker with both diagnostic and prognostic utility across multiple cancer types, especially PAAD, underscoring its potential as a promising therapeutic target for cancer immunotherapy. Clinical trial number Not applicable.